Challenges in the Measurement of LUSI’s Physical Properties - Hamdi Rifai; Satria Bijaksana; Umar Fauzi; Bagus E. B. Nurhandoko (Indonesian Journal of Physics, 2007)
An extraordinary mud volcano, commonly referred to as LUSI or Lumpur (mud) Sidoarjo, erupted in May of 2006 in Sidoarjo, East Java. Since then, LUSI has claimed approximately 700 hectares of rice fields, factories, villages and other infrastructures. A bold attempt to reduce the volume of mud by inserting sets of high density chained balls (HDCB) has been tried by a team of scientists and engineers from Bandung Institute of Technology. This effort requires, among others, measurement of LUSI’s physical properties (temperature, density, water content, viscosity, magnetic susceptibility, etc.) as a part of its evaluation and monitoring system. We will describe how this challenging task was performed. The environment in which the samples were obtained is harsh as the in situ temperature of the mud is about 90 degree centigrade, the ground in unstable, and the presence of water vapor with high content of H2S. In general, mud samples were collected on daily basis during the HDCB insertion. The results of these measurements of physical properties are valuable in assessing the effectiveness of the HDCB operation.